HERBAL PRODUCT USE BY THE CANCER PATIENTS IN BOTH THE PRE AND POST SURGERY PERIODS AND DURING CHEMOTHERAPY - KoÃ§aÅŸlÄ±, Sema; Demircan, Zehra (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: The aim of this study was to evaluate of the use of herbal products in patients in both pre- and postsurgeryperiods and during chemotherapy, and to determine the factors behind it.Materials and Methods: This study was conducted as a descriptive study with 281 patients in 4 centers. The data ofthe study were collected by using a survey form prepared by the researcher, depending on literature and interview withthe participants face-to-face.Results: While the average age of the patients involved in the study is 49.1±12.8, 51.6% of them were females, 34.6%graduate of elementary school, and 34.5% were housewives. While the prevelance of the use of herbal product prior tosurgical treatment is 38.9%, it was observed that this rate increased to 54.1% during chemotherapy. It was observedthat the most frequently used product was garlic prior to surgical treatment (19.2%), that it was urtica dioica (13.8%)during chemotherapy. Before the surgical treatment, 94.3% of the patients, and during chemotherapy treatment, 81.7%of the patients, stated that the use of herbal product had not been questioned by the physician or nurse.Conclusion: Analysis of the results indicates that health professionals need to obtain information regarding the use ofherbal products by cancer patients during both pre- and post- surgery periods, as well as during chemotherapy. Patientsshould be provided with information and guidance about the advantages and disadvantages of using herbal products.